2021
DOI: 10.1093/ecco-jcc/jjab219
|View full text |Cite
|
Sign up to set email alerts
|

Western and Carnivorous Dietary Patterns are Associated with Greater Likelihood of IBD Development in a Large Prospective Population-based Cohort

Abstract: Objective Nutrition plays a role in the development of Crohn’s disease (CD) and ulcerative colitis (UC). However, prospective data on nutrition and disease-onset is limited. Here, we analysed dietary patterns and scores to IBD-development in a prospective population-based cohort. Design We analysed 125,445 participants of whom 224 individuals developed de novo UC and 97 CD over a maximum 14-year follow-up period. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 52 publications
(57 reference statements)
1
37
0
Order By: Relevance
“…In the study of Khalili et al, a greater adherence to MD was associated with a significantly lower risk of later-onset CD (age, gender, education level, body mass index and smoking did not modify these associations), but not UC [12]. On the other hand, WD was associated with a greater likelihood of CD development and a carnivorous pattern with UC development [223]. Additionally, adherence to MD was associated with an improvement in quality of life among individuals suffering from CD (IBDQ score) [224].…”
Section: Is the Mediterranean Diet An Alternative To The Western Diet...mentioning
confidence: 90%
“…In the study of Khalili et al, a greater adherence to MD was associated with a significantly lower risk of later-onset CD (age, gender, education level, body mass index and smoking did not modify these associations), but not UC [12]. On the other hand, WD was associated with a greater likelihood of CD development and a carnivorous pattern with UC development [223]. Additionally, adherence to MD was associated with an improvement in quality of life among individuals suffering from CD (IBDQ score) [224].…”
Section: Is the Mediterranean Diet An Alternative To The Western Diet...mentioning
confidence: 90%
“…The fourth dietary pattern was characterised by a high intake of coffee and alcohol, in contrast to a low intake of tea and moderate consumption of spreads and dairy [6]. This pattern was strongly associated with higher levels of plasma CCL11, but with lower levels of plasma IL12B.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies observed that dietary patterns are strongly associated with a greater likelihood of IBD development [6], pro-inflammatory gut microbial signatures [7], intestinal inflammation and disease exacerbations in established IBD [8][9][10][11]. A myriad of studies linked specific dietary components to inflammatory markers such as CRP or FCal or used various in vitro and in vivo approaches to uncover pro-inflammatory or anti-inflammatory effects [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• More than one-third of young patients with IBD and their parents believe that diet has a significant role in the course of IBD. To date, even if no single food substance has been identified as causative of IBD onset or relapse, a high intake of snacks, prepared meals, carbonated beverages, and sauces with low vegetables and fruit has been associated with a greater likelihood of CD development and a carnivorous pattern with UC development (4).…”
Section: What Is Newmentioning
confidence: 99%